Comparison of Low and High Temperature Sintering for Processing of Bovine Bone as Block Grafts for Oral Use: A Biological and Mechanical In Vitro Study - Asrar Elahi; Warwick Duncan; Kai-Chun Li; John Neil Waddell; Dawn Coates (Bioengineering, 2023)
Large oral bone defects require grafting of bone blocks rather than granules to give physically robust, biocompatible and osteoconductive regeneration. Bovine bone is widely accepted as a source of clinically appropriate xenograft material. However, the manufacturing process often results in both reduced mechanical strength and biological compatibility. The aim of this study was to assess bovine bone blocks at different sintering temperatures and measure the effects on mechanical properties and biocompatibility. Bone blocks were divided into four groups; Group 1: Control (Untreated); Group 2: Initial boil for 6 h; Group 3: Boil 6 h followed by sintering at 550 °C for 6 h; Group 4: Boil 6 h followed by sintering at 1100 °C for 6 h. Samples were assessed for their purity, crystallinity, mechanical strength, surface morphology, chemical composition, biocompatibility and clinical handling properties. Statistical analysis was performed using one-way ANOVA and post-hoc Tukey’s tests for normally distributed and Friedman test for abnormally distributed quantitative data from compression tests and PrestoBlue™ metabolic activity tests. The threshold for statistical significance was set at p < 0.05. The results showed that higher temperature sintering (Group 4) removed all organic material (0.02% organic components and 0.02% residual organic components remained) and increased crystallinity (95.33%) compared to Groups 1–3. All test groups (Group 2–4) showed decreased mechanical strength (MPa: 4.21 ± 1.97, 3.07 ± 1.21, 5.14 ± 1.86, respectively) compared with raw bone (Group 1) (MPa: 23.22 ± 5.24, p <0.05), with micro-cracks seen under SEM in Groups 3 and 4. Group 4 had the highest biocompatibility (p < 0.05) with osteoblasts as compared to Group 3 at all time points in vitro. Clinical handling tests indicated that Group 4 samples could better withstand drilling and screw placement but still demonstrated brittleness compared to Group 1. Hence, bovine bone blocks sintered at 1100 °C for 6 h resulted in highly pure bone with acceptable mechanical strength and clinical handling, suggesting it is a viable option as a block grafting material.